(untitled) (Journal of the College of Basic Education, 2023)
In this research, we have dealt with the subject of (Quranic purposes according to Imam Al-Sabouni in his interpretation, Safwat Al-Tafseer), which represents the broadcast of a detective and a teacher. So we presented in the first research (Faith in God), then this topic included three demands, which are the unification of divinity, the unification of names and attributes, and the unification of divinity As for the second research, it was (belief in messengers and prophets), in which the Quranic verses dealt with the necessity of believing in messengers and prophets, the characteristics and features of the call of the prophets, revelation, proof of prophecy, miracles, and the characteristics of the Muhammadan message. As for the third topic, it was (belief in angels). It dealt with the noble Quranic verses through seven demands of the obligation to believe in angels and their attributes, the moral and congenital attributes of angels, the number of angels and their names, the worship of angels, the actions of angels, and the plots of Satan in matters of belief in angels, and the comparison between angels and humans, and then The conclusion is followed by the sources and references